Madrasah: Sejarah dan Dinamikanya - Zainuddin Zainuddin (At-Tafkir, 2021)
The long journey of madrasas cannot be separated from the long history of this world. Its existence which is full of twists and turns in order to maintain the existence of Islam becomes something unique to him. Since Indonesia's independence even long before that, the madrasa has contributed a lot in educating the lives of Muslim communities. Although in its journey, it always gets a stumbling around the regulations. The dynamics they experience make madrasa always up to date to discuss.